Determinants of Household Water Supply Sustainability in an Emerging Town in Northwest Ethiopia - Workneh, Fekadu; Belay, Mehretie (Ethiopian Journal of Social Sciences, 2020)
Accessing useable freshwater appears to be the main worry of urban citizens in Ethiopia today. The possible reasons for the problem are not yet duly addressed in scientific literatures. In this paper we analyzed the determinants of household water supply and sustainability in a rural town named Agew-Gimjabeht, Ethiopia. We captured data through questionnaires, interviews, discussions and observations. Data were analyzed using descriptive statistics and the binary logistic regression model. We found that many households (â‰¥68%) lack adequate water supply to satisfy their family needs. The daily household per capita water was 42.13 liters. The per capita water (9.93 liter per person per day/ l p -1 d -1 ) found less than the universally recommended 20 l p -1 d -1 threshold. Age, house type, micro-relief, rate of urbanization and management capacity significantly influenced householdsâ€™ freshwater sustainability in the town. It is recommended that urban governments design better urban management schemes and capacities to minimize water shortages.